Development of tools to target antigen through mannose receptor - Abbas, Zaigham (2011)
Dendritic cells (DC) are unique antigen presenting cells which play a major role in antigen presentation and initiation of the immune response by regulating B- and T- cell activation. Antigen targeting to DC receptors is an effective, safe and specific method for vaccine development. The mannose receptor (MR) is an endocytic receptor expressed by subpopulations of DC and antigen targeting through MR leads to enhanced antigen uptake and presentation to T -cells. This makes MR a favourite receptor for the development of vaccines against diseases that require T-cell immunity such as cancer and viral infections. This project sought to develop tools to target antigens through MR and investigate their ability to induce T-cells activation in vitro and in vivo. We have used three approaches to deliver antigen through MR; (i) MRspecific mAbs: 503 and 6C3, have been chemically linked to the melanoma epitope TRP-2, (ii) MR-specific chimeric antibodies carrying several model antigens have been generated by using genetic engineering and (iii) Glycopolymers and the suitable antigens such as a shorter version of model antigen ovalbumin (OVA), with and without N-glycosylation sites have been generated and characterised. Glycopolymer-OVA conjugates were prepared by chemical coupling but it requires further optimization. The binding efficiency of anti-MR antibodies has been assessed using ELISA and BIACORE and the glycopolymers have been tested for their interaction with MR. Immunisations were performed with anti-MR mAb-TRP2 conjugates which induced TRP-2 specific COS+ T-cells activation and improved humoral response. Due to limitations in this approach in terms of chemical coupling being an inefficient method and the potential involvement of Fc recetors (FcRs), chimeric Abs fused to model antigens and bearing mutated Fc were generated. These chimeric Abs, have been tested for their ability to induce T-cell activation in vitro and in vivo. But the progress has been hampered due to the labile nature of these reagents. In future, anti-MR chimeric Abs will be used to generate anti-MR single chain antibodies carrying OVA (ScFv-OVA) and the glycopolymer project will be taken up Dr. Manovani Giuseppe (School of Pharmacy, University of Nottingham). It will involve further optimization of chemical coupling of glycopolymers to a-glycosylated OVA-mini protein, and the in vitro Ag presentation assay to investigate whether glycopolymers mediated Ag targeting of APe enhance T-cells activation. These further studies would greatly benefit the understanding of the mechanisms associated with the elicitation of immune resposes as a result of Ag targeting through MR. Anti-MR reagents generated in this study along with appropriate adjuvant could be exploited to target malarial, cancerous and viral Ags for robust T-cell activation against these infectious diseases. On the other hand, the role of MR in homeostasis and allergy has been already established, and the anti-MR reagents generated in this study can be used to target allergens and self-Ags to APes in an attempt to induce tolerance.